Character Education Values on Novel âSepatu Dahlanâ by Khrisna Pabichara: Critical Reading - Gusnetti, Gusnetti; Agustina, Agustina; Ermanto, Ermanto (Proceedings of the UR International Conference on Educational Sciences, 2018)
This article discusses the values of character education in the novel âSepatu Dahlanâ by Khrisna Pabichara. The theory used in this article is guided by the article Tarigan (2009), Ermanto (2012), Ulinnuha (2013), Karnasa (2013), Gusnetti (2014), Jalilihar et al. (2015), Kulkarni et al (2015), Tornberg (2016), Sriwimon (2017) Sanz (2017). This research was carried out with qualitative research with descriptive methods. The results showed that there were 15 characters of education found in the novelâ Sepatu Dahlanâ by Khrisna Pabichara, on the other hand, religious, honest, responsible, disciplined, hard work, creative, independent, democratic, curiosity, achievement, communicative, peaceful love, environment care, social care, and responsibility. Thus it can be concluded that novel âSepatu Dahlanâ can be implied in Indonesian language subjects in high school based on the 2013 curriculum.